Detection of type III effector‐induced transcription factors that regulate phytohormone content during symbiosis establishment in soybean. Issue 2 (7th March 2023) - Lu, Wencheng; Zheng, Zefeng; Kang, Qinglin; Liu, Hongji; Jia, Hongchang; Yu, Fenghao; Zhang, Yuxin; Han, Dezhi; Zhang, Xiaoyuan; Yan, Xiaofei; Huo, Mingqi; Wang, Jinhui; et al.
Abstract: Soybean is a pivotal protein and oil crop that utilizes atmospheric nitrogen via symbiosis with rhizobium soil bacteria. Rhizobial type III effectors (T3Es) are essential regulators during symbiosis establishment. However, how the transcription factors involved in the interaction between phytohormone synthesis and type III effectors are connected is unclear. To detect the responses of phytohormone and transcription factor genes to rhizobial type III effector NopAA and type III secretion system, the candidate genes underlying soybean symbiosis were identified using RNA sequencing (RNA‐seq) and phytohormone content analysis of soybean roots infected with wild‐type Rhizobium and its derived T3E mutant. Via RNA‐seq analysis the WRKY and ERF transcription factor families were identified as the most differentially expressed factors in the T3E mutant compared with the wild‐type. Next, qRT‐PCR was used to confirm the candidate genes Glyma.09g282900, Glyma.08g018300, Glyma.18g238200, Glyma.03g116300, Glyma.07g246600, Glyma.16g172400 induced by S. fredii HH103, S. fredii HH103ΩNopAA, and S. fredii HH103ΩRhcN. Since the WRKY and ERF families may regulate abscisic acid (ABA) content and underlying nodule formation, we performed phytohormone content analysis at 0.5 and 24 h post‐inoculation (hpi). A significant change in ABA content was found between wild Rhizobium and type III effector mutant. Our results support that NopAA can promote the establishment of symbiosis by affecting the ABA signaling pathways by regulating WRKY and ERF which regulate the phytohormone signaling pathway. Specifically, our work provides insights into a signaling interaction of prokaryotic effector‐induced phytohormone response involved in host signaling that regulates the establishment of symbiosis and increases nitrogen utilization efficiency in soybean plants.